Puglisi, Puritans Besieged - The Legacies of King Philip’s War in the Massachusetts Bay Colony - Quinlivan, Mary (Teaching History: A Journal of Methods, 1994)
In this well organized and generally readable volume, Michael Puglisi discusses the significance of King Philip’s War of 1675-76 in New England society during the last quarter of the seventeenth century. Under the leadership of Metacom (King Philip), native Americans carried on the single greatest challenge to the New England colonists. After fifteen months of conflict, the war ended with Metacom’s death in August 1676. According to Puglisi, the legacies of the war were to live long after Metacom and have grave effects on Puritan society for the remainder of the century.